The Digital Stethoscope with the Heart Rate Display: A Review and Its Implications for Learning - Fuady, Khairul; Nanda, Nanda; Zulisa, Eva (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2024)
A stethoscope is an important medical tool for initial examination of a patient's heartbeat, including detection of arrhythmias (heart rhythm disturbances). This digital stethoscope equipment has input voltage specifications from a power supply of +6 Volt DC and +12 Volt DC, condenser mic as a stethoscope sensor, LED as a heart rate indicator, seven segments as a heartbeat display and timer, earphones as a tool for hearing sounds heartbeat and amplifier circuit. The research was carried out using system operations and supporting blocks to analyze the results of tool testing. The voltage measurements in the tool support block were obtained according to the plan, the start timer circuit voltage was 4.6 VDC (working), the NE555N IC output voltage was 5.8 VDC and the voltage at the transistor collector leg was measured when the condenser microphone received a sound signal. A digital stethoscope can display heartbeats for a duration of 15 seconds, so it still requires manual calculations to determine the heartbeat for 1 minute. Based on the test results, this Stethoscope will be an effective learning aid to improve students' medical skills